Telerehabilitation: A Practical Remote Alternative for Coaching and Monitoring Physical Kinetic Therapy in Patients with Mild and Moderate Disabling Parkinson’s Disease during the COVID-19 Pandemic - Aurelian Anghelescu (Parkinson's Disease)
Background. The COVID-19 pandemic imposed social/physical distancing, lockdown measures, and forced reorientation of the rehabilitation programs for people with Parkinson’s disease (PD). Epidemiologic safety measures boosted remote exercise-based treatment. Objectives. Remote delivery of rehabilitation care services is not typically used in our department. Therefore, this study aimed to assess and implement a telehealth physical rehabilitation program tailored for outpatients with idiopathic PD and slight or medium functional limitations. Methods. A prospective study was performed on a group of outpatients with idiopathic PD, selected from the database of the neurorehabilitation clinic of the Emergency Teaching Hospital “Bagdasar-Arseni.” We studied 17 patients (5 women and 12 men), aged between 54-70 years (average 65.9 ± 4.87), with a disease history of 7.3 ± 3.6 (years), with mild or moderate disabling clinical forms, quantified by an average Hoehn and Yahr score of 2.3 ± 0.35 (limits 1.5-3). All patients underwent pharmacologic treatment with unchanged doses throughout the study. No patients had disabling osteoarticular problems (all could walk independently) and had no significant psycho-cognitive dysfunction. Patients were supervised and coached online in tandem by the therapist and physician. In addition, a family member assisted and supervised the patient’s performance and coordinated the technical electronic procedures. Walking biodynamics was assessed by timing “6-meters walking” and “Get up and walk 3 meters” (TUG) tests. Each person attended ten sessions of motor telerehabilitation procedures (2 per week) lasting 50 minutes each during social distancing (October-December 2021). Results. None of the patients was at increased risk of falling. They all improved their locomotor performance, reflected in a significant decrease in TUG duration (the initial average time improved from 13.50 seconds to 10.57). The telerehabilitation program also significantly improved the average walking speed (initially, 44.5 cm/sec and finally, it raised to 56.8 cm/sec). Discussion. The TUG and “6-meters walking” tests are helpful tools for a global biodynamic remote assessment of PD patients. Limitations of the study: a small group of selected patients, restrictive working conditions (due to epidemiological social/physical restrictions and no direct physiotherapist-patient contact), and need for supervision by an attendant to assist the subject and perform the audio-video transmission. Further studies are necessary to identify the optimal web-based model of care and boost the implementation of this modern neurorehabilitation concept. Conclusions. Telemedicine turned the virtual space into a new reality and may compensate for the restrictions imposed on face-to-face meetings in pandemic conditions. Moreover, with modern telecommunication techniques, a regular and individualized physical kinetic rehabilitation program can be performed even in pandemic conditions. Remote delivery of kinetic motor programs was appropriate for selected groups of PD patients.